Multispectroscopic Study of the Interaction of Chloramphenicol with Human Neuroglobin. Issue 3 (3rd June 2012) - Huang Huang, Lei Lei; Li Li, Lianzhi Lianzhi; Li Li, Haili Haili; Gao Gao, Chaohui Chaohui; Cui Cui, Hui Hui; Tan Tan, Xiangshi Xiangshi
Abstract : The interaction between chloramphenicol (CHL) and neuroglobin (Ngb) has been investigated by using fluorescence, synchronous fluorescence, UV-Vis and circular dichroism (CD) spectroscopy. It has been found that CHL molecule can quench the intrinsic fluorescence of Ngb in a way of dynamic quenching mechanism, which was supported by UV-Vis spectral data. Their effective quenching constants (K SV ) are2.2 × 10 4, 2.6 × 10 4, and 3.1 × 10 4  L·mol −1 at 298 K, 303 K, and 308 K, respectively. The enthalpy change (Δ H ) and entropy change (Δ S ) for this reaction are 26.42 kJ·mol −1 and 171.7 J·K −1, respectively. It means that the hydrophobic interaction is the main intermolecular force of the interaction between CHL and Ngb. Synchronous fluorescence spectra showed that the microenvironment of tryptophan and tyrosine residues of Ngb has been changed slightly. The fluorescence quenching efficiency of CHL to tyrosine residues is a little bit more than that to tryptophan residues of Ngb. Furthermore, CD spectra indicated that CHL can induce the formation of α -helix of Ngb.